JOB SATISFACTION AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR MEASUREMENT MODEL ON PERMANENT LECTURER CASE STUDY AT PRIVATE ISLAMIC UNIVERSITY IN MEDAN CITY - Muslih, Muslih; Jufrizen, Jufrizen (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
This study aims to find out how to measure job satisfaction and organizational citizenship behavior for permanent lecturers, a case study at a private Islamic university in Medan at a private Islamic university in Medan. While the specific objectives are 1). Identifying the level of Job Satisfaction of lecturers at the Private Islamic University in Medan City, 2). Studying the factors that affect the Job Satisfaction of lecturers at a private Islamic University in Medan City. The study population was all permanent lecturers at private Islamic universities in Medan, namely Muhammadiyah University of North Sumatra, Islamic University of North Sumatra, Muslim Nusantara University Al-Washliyah, Al-Washliyah University and Al-Azhar University. However, in this study it is only limited to Islamic universities owned by the Islamic Foundation (Islamic Organization), namely UMSU and UMN, totaling 425 permanent lecturers who have functional positions as Expert Assistant, Lector and Head Lector. The sampling technique in this study was carried out using a proportional random sample or proportional random sampling and obtained as many as 219 people. The data analysis method used in this research is the Structural Equation Model method. The results of this study indicate that Spiritual Leadership, Self Efficacy, Locus of Control affect Organizational citizenship behavior. Spiritual Leadership, Self Efficacy, Locus of Control affect Job Satisfaction. Spiritual Leadership has an effect on Job Satisfaction through Organizational citizenship behavior. Self Efficacy has an effect on Job Satisfaction through Organizational citizenship behavior. Locus of Control has an effect on Job Satisfaction through Organizational citizenship behavior